Peningkatan Pengetahuan Ibu Balita Melalui Sosialisasi Pencegahan Stunting di Desa Madusari, Kecamatan Secang, Kabupaten Magelang - Muktivani Swastiko; Istiqomah Nur Cahayani; Rahma 'Aina Zulfa; Elsina Anbiya Sahnaj; Winda Maulana; Risma Elly Zuliyanti; Amanda Della Octavioni; Ardi Darmawan; Muhammad Rivaldy; Muhammad Arham Farizy (Universitas Tidar, 2026)
Stunting is a chronic nutritional problem that is currently a public health challenge, especially at the village level. This community service activity aims to increase the knowledge and insight of mothers of toddlers regarding stunting prevention through an understanding of appropriate parenting patterns and healthy environmental management. The service was held in Madusari Village, Secang District, Magelang Regency. The outreach was carried out using a Participatory Action Research (PAR) approach involving Posyandu cadres and mothers of children aged one to three years. The implementation method included a preparation stage, implementation of outreach through interactive lectures, discussions, and evaluation using pre-test and post-test instruments . The results of the outreach showed an increase in the average knowledge score of participants from 88.2 in the pre-test to 95.2 in the post-test , indicating an increase in participants' understanding of stunting prevention efforts. Thus, this outreach activity has proven effective as a means of public health education and can encourage efforts to accelerate stunting reduction at the village level by increasing the knowledge and insight of mothers of toddlers.